Ms. Marvel. The new mutant Vol. 1 - Vellani, Iman; Pirzada, Sabir; Wilson, G. Willow, 1982- (Marvel Worldwide, Inc., 2023)
"Kamala Khan is back - and she's an X-Man! Ms. Marvel bursts into the next phase of her life in an exciting adventure co-written by Iman Vellani, the MCU's own Kamala, and Sabir Pirzada of both DARK WEB: MS. MARVEL and her Disney+ series! That's right - the good news is that in the wake of her recent world-saving sacrifice, Ms. Marvel has been resurrected via Krakoan technology! What a way to learn she's both an Inhuman AND a mutant! The bad news is that her debut at the Hellfire Gala didn't go exactly as planned, and now all of mutantkind is being hunted worldwide! Plunged into a world of hate and fear, Kamala has a secret mission to pull off for the X-Men! Can an undercover Kamala infiltrate Orchis itself even as she struggles to acclimate to this new part of her identity?"--Amazon.